Melatonin and Aromatase in Breast Cancer - Cos, Samuel; Martinez-Campa, Carlos; V. Gonzalez, Alicia; Alvarez-García, Virginia; Alonso-González, Carolina; Dolores Mediavilla, M.; J. Sanchez-Barcelo, Emilio (Clinical Cancer Drugs, 2014)
It has been shown that melatonin, the pineal gland hormone, is an oncostatic agent that arrests the growth of different kinds of tumors, especially mammary tumors whose growth is dependent of estrogens. In vivo and in vitro previous reports point to the hypothesis that melatonin interplays with estrogen-signaling pathways at three different levels: (a) an indirect mechanism, by interfering with the hypothalamic-pituitary-reproductive axis, in such way that the level of plasma estrogens synthesized by the gonadal glands are down-regulated, (b) direct mechanism of the melatonin at cell cancer level, disrupting the activation of estradiol receptors, therefore behaving as a selective estrogen receptor modulator (SERM), and finally (c) by regulating the enzymes involved in the biosynthesis of estrogens in other tissues, thus behaving as a selective estrogen enzyme modulator (SEEM). Melatonin has been proved to alter both the activity and expression of several enzymes implicated in steroidal hormones synthesis, such as aromatase, the complex necessary to convert androgens into estrogens, in different kind of cells, such as malignant epithelial cells from breast cancer and cells surrounding the tumor: fibroblasts and endothelial cells, therefore protecting the mammary gland from estrogen induced proliferation and transformation. The aim of the present review is to summarize the recent findings describing how melatonin is able to modulate aromatase. Antiaromatase drugs are currently employed in breast cancer therapy and therefore melatonin modulation of aromatase points to this indolamine as a potential anticancer drug in estrogen-dependent mammary cancer prevention and treatment.
Keywords: MCF-7